2020
DOI: 10.1155/2020/5271657
|View full text |Cite
|
Sign up to set email alerts
|

First Serological Study Revealing High Humoral Response and Evidence for Antigenic Heterogeneity in Leishmania donovani Induced CL in Sri Lanka

Abstract: Posing a threat to the ongoing leishmaniasis elimination efforts in the Indian subcontinent, L. donovani-induced cutaneous leishmaniasis (CL) has been recently reported in many countries. Sri Lanka reports a large focus of human cutaneous leishmaniasis (CL) caused by Leishmania donovani, a usually visceralizing parasite. Enhanced case detection, early treatment, and in-depth understanding of sequalae are required to contain the spread of disease. Visceralizing potential of dermotropic strains has not been full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Further, with Leishmania being an intracellular pathogen, the total of T-cell immunity comprising heterogeneous T-cell subsets with discrete effector cytokines direct the course of the disease ranging from non-symptomatic to mild-to-severe VL and CL phenotypes ( 14 , 16 , 17 , 21 , 22 ). With substantial insight into the host immune correlates that underline the classical visceral and cutaneous manifestation, scarce reports are available on host immune correlates in L. donovani atypical CL disease emerging in known and newer endemic sites in the Indian subcontinent ( 10 , 30 32 , 35 , 36 ). Knowledge on comparative host immune response in LdCL versus typical VL is important to define the key immune checkpoints that can modulate the disease towards atypical phenotype ( 9 12 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, with Leishmania being an intracellular pathogen, the total of T-cell immunity comprising heterogeneous T-cell subsets with discrete effector cytokines direct the course of the disease ranging from non-symptomatic to mild-to-severe VL and CL phenotypes ( 14 , 16 , 17 , 21 , 22 ). With substantial insight into the host immune correlates that underline the classical visceral and cutaneous manifestation, scarce reports are available on host immune correlates in L. donovani atypical CL disease emerging in known and newer endemic sites in the Indian subcontinent ( 10 , 30 32 , 35 , 36 ). Knowledge on comparative host immune response in LdCL versus typical VL is important to define the key immune checkpoints that can modulate the disease towards atypical phenotype ( 9 12 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Promastigote forms of L. donovani grown in complete medium 199 at late log phase were harvested. 27 The culture was subjected to centrifugation at 15,000 rpm for 10 min and the isolated pellet was freeze-thawed (frozen in liquid nitrogen and thawed at 37 C) five times. The suspension was disrupted with a syringe (21G needle) a couple of times and the cell debris was pelleted down at 1000 rpm for 5 min.…”
Section: Preparation Of Leishmania Soluble Antigenmentioning
confidence: 99%
“…Previous studies on CL patients which evaluated the rK39 antibody response 24 and expression of peroxidoxin antigen of Leishmania amastigotes using commercially available immunodiagnostic assays showed low sensitivity in the local setting. 25 Demonstration of a high seroprevalence in L. donovani-induced CL in recent local studies 26,27 warrants further evaluation of these humoral immune responses at different clinical stages.…”
mentioning
confidence: 99%
“…Recent studies in Sri Lanka have estimated a seroprevalence rate of 34% among CL cases [ 20 ]. A follow-up study revealed a higher seroprevalence of 82% using crude protein lysate of the local dermatropic strain [ 21 ]. Even though CL in Sri Lanka is caused by L. donovani , a normally visceralizing parasite, the rK39 antibody detection has been consistently low in Sri Lanka [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%